A no????o de comunica????o p??blica na implanta????o da TV digital no Brasil e na Argentina: estudo comparativo - Mateus, Tatiane Rodrigues (2017)
This research does a historical analysis, in methodological terms .The temporal cut is eight years (2006-2014). This study aims to provide answers about Argentine and Brazilian public television in face of digital age. This search was based on theoretical background in public communication and Digital TV. These studies enable a perception the public digital television as a social development instrument. It dialogues with public communication and international relations focusing on ISDB-T on Brazil and Argentina with emphasis on Public Communication.